Pelembagaan Hukum Islam di Sumatera Timur: Tinjauan Historis - Jumanah Nasution; Zainul Fuad (LPPM Universitas Ekasakti Padang, 2023)
The institutionalization of Islamic law has long roots in the life history and collective memory of the Indonesian Muslim community; Reflected in various proverbs such as